Note on transmitted complexity for quantum dynamical systems. (13th November 2017) - Watanabe, Noboru; Muto, Masahiro
Abstract : Transmitted complexity (mutual entropy) is one of the important measures for quantum information theory developed recently in several ways. We will review the fundamental concepts of the Kossakowski, Ohya and Watanabe entropy and define a transmitted complexity for quantum dynamical systems. This article is part of the themed issue 'Second quantum revolution: foundational questions'.